Approach to detector design for statistical multiple-input–multiple-output radars using multi-scan data - Sharify, Soroush; Nayebi, Mohammad Mahdi (IET radar, sonar & navigation, 2017)
This study considers the detector design and performance analysis in a statistical multiple-input–multiple-output radar. The authors studied this subject under some assumptions such as single point target, Swerling scattering models for radar cross-section and Gaussian interference. The target is assumed to move in a piecewise linear trajectory and multi-scan data is stored. So, the target cell may have changed during the time. A three-dimensional data signal space is generated that involved in observations from multiple scans, then a generalised likelihood ratio test detector is derived that employs consecutive observations in a central unit. Then a sub-optimum detector is introduced in which each pair of transmitters–receivers works separately and the central unit decides with a binary algorithm. The exact theoretical performances of both detectors are extracted and their qualities are compared. Numerical simulations verify all results.